Foreign Employment, Income Shifting, and Tax Uncertainty - Drake, Katharine D.; Goldman, Nathan C.; Murphy, Francis (The Accounting Review, 2022)
ABSTRACT We examine the effect of foreign employment on two outcomes—income shifting and the tax uncertainty of foreign transactions. Using a hand-collected sample of employment disclosures, we partition our sample into firm-years with a higher or lower degree of foreign employment. Using two distinct income shifting models, we document that, on average, a high degree of foreign employment is associated with greater tax-motivated income shifting out of the U.S. We also posit and find that a high degree of foreign employment enhances the economic substance of foreign transactions, reducing the tax uncertainty associated with foreign income. We conduct additional analyses to mitigate selection bias concerns, and we use exogenous changes to the costs and benefits of income shifting using foreign employment to strengthen identification. Our results highlight firms' use of employees as part of a tax-efficient supply chain and how foreign employment enhances income shifting opportunities between jurisdictions.